2019
DOI: 10.2196/14571
|View full text |Cite
|
Sign up to set email alerts
|

A Mobile App to Support Parents Making Child Mental Health Decisions: Protocol for a Feasibility Cluster Randomized Controlled Trial

Abstract: Background Shared decision making (SDM) is recognized as a person-centered approach to improving health care quality and outcomes. Few digital interventions to improve SDM have been tested in child and adolescent mental health (CAMH) settings. One such intervention is Power Up, a mobile phone app for young people (YP), which has shown some evidence of promise that YP who received Power Up reported greater levels of SDM. However, even though parents play a critical role in CAMH care and treatment, t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 57 publications
0
6
0
Order By: Relevance
“…Parents were recruited from England in two strands: (1) as part of a feasibility and acceptability trial within the National Health Services ( 45 ), and (2) through social media platforms or in-person advertising. Parents were eligible if they (1) had at least one child or young person (0–24 years) with a mental health problem, (2) were over the age of 18, (3) had no known diagnosed mental health problems and (4) had the ability to speak and understand English.…”
Section: Methodsmentioning
confidence: 99%
“…Parents were recruited from England in two strands: (1) as part of a feasibility and acceptability trial within the National Health Services ( 45 ), and (2) through social media platforms or in-person advertising. Parents were eligible if they (1) had at least one child or young person (0–24 years) with a mental health problem, (2) were over the age of 18, (3) had no known diagnosed mental health problems and (4) had the ability to speak and understand English.…”
Section: Methodsmentioning
confidence: 99%
“…In keeping with the MRC framework, the intervention then entered the pilot and feasibility phase for testing the intervention, as discussed in the study protocol [ 56 ]. Preliminary results of the feasibility study [ 57 ] indicated that the intervention itself is generally acceptable by parents, carers, and health care professionals.…”
Section: Discussionmentioning
confidence: 99%
“…The development and evidence base for the PUfP prototype are described and outlined in more detail in the study protocol [ 17 ]. PUfP is a decision support intervention with 5 key features (ie, decisions, goals, journey, support, and resources).…”
Section: Methodsmentioning
confidence: 99%
“…These consisted of demographic details (gender, ethnicity, first language, relationship to child, and child’s age), participation rates (completion of consent, pretest and posttest measures, and intervention use), SDM measures (the Control Preferences Scale for Pediatrics [ 31 ], the Pediatric Shared Decision-Making Questionnaire (modified) [ 32 ], and the Decisional Conflict Scale [DCS] [ 33 ]), experience of service (the Experience of Service Questionnaire [ESQ] [ 34 ]), usability and acceptance (the Poststudy Usability Questionnaire [ 35 ]), and an anxiety measure (the Spielberger State Anxiety Inventory Form for Adults [ 36 ]). Further details on the outcome measures are presented in the study protocol [ 17 ]. Depending on which group the participants were recruited into (ie, IG1, IG2, or control), they received help to access the app and were given a guided tour.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation